Fluoxetine enhances synaptic vesicle trafficking and energy metabolism in the hippocampus of socially isolated rats - Filipović, Dragana; Costina, Victor; Findeisen, Peter; Inta, Dragos (International journal of molecular sciences, 2022)
Chronic social isolation (CSIS)-induced alternation in synaptic and mitochondrial function of specific brain regions is associated with major depressive disorder (MDD). Despite the wide number of available medications, treating MDD remains an important challenge. Although fluoxetine (Flx) is the most frequently prescribed antidepressant, its mode of action is still unknown. To delineate affected molecular pathways of depressive-like behavior and identify potential targets upon Flx treatment, we performed a comparative proteomic analysis of hippocampal purified synaptic terminals (synaptosomes) of rats exposed to six weeks of CSIS, an animal model of depression, and/or followed by Flx treatment (lasting three weeks of six-week CSIS) to explore synaptic protein profile changes. Results showed that Flx in controls mainly induced decreased expression of proteins involved in energy metabolism and the redox system. CSIS led to increased expression of proteins that mainly participate in Ca2+/calmodulin-dependent protein kinase II (Camk2)-related neurotransmission, vesicle transport, and ubiquitination. Flx treatment of CSIS rats predominantly increased expression of proteins involved in synaptic vesicle trafficking (exocytosis and endocytosis), and energy metabolism (glycolytic and mitochondrial respiration). Overall, these Flx-regulated changes in synaptic and mitochondrial proteins of CSIS rats might be critical targets for new therapeutic development for the treatment of MDD.
Gesehen am 05.06.2023